Infectious diseases in humanized mice. Issue 9 (5th September 2013) - Leung, Carol; Chijioke, Obinna; Gujer, Cornelia; Chatterjee, Bithi; Antsiferova, Olga; Landtwing, Vanessa; McHugh, Donal; Raykova, Ana; Münz, Christian
<x xml:space="preserve">Abstract</x> Despite many theoretical incompatibilities between mouse and human cells, mice with reconstituted human immune system components contain nearly all human leukocyte populations. Accordingly, several human‐tropic pathogens have been investigated in these in vivo models of the human immune system, including viruses such as human immunodeficiency virus (HIV) and Epstein‐Barr virus (EBV), as well as bacteria such as Mycobacterium tuberculosis and Salmonella enterica Typhi. While these studies initially aimed to establish similarities in the pathogenesis of infections between these models and the pathobiology in patients, recent investigations have provided new and interesting functional insights into the protective value of certain immune compartments and altered pathology upon mutant pathogen infections. As more tools and methodologies are developed to make these models more versatile to study human immune responses in vivo, such improvements build toward small animal models with human immune components, which could predict immune responses to therapies and vaccination in human patients.